Product Creativity, Branding, and Marketing in the Tempe Business: A Case Study of the All Tempe Production House - Indra Kumala; Syaila Nabila; Asri Amaliyah Asri (Yayasan Bayt Shufiya Nusantara, 2025)
The tempeh industry in Indonesia is undergoing a transformation from household-based production to medium-scale industries aimed at marketing products to modern retail markets. This study examines how creativity in product development and branding strategies are employed to enhance competitiveness at Sangat Tempe Factory in Medan, which focuses on large retail stores as its primary distribution channels. This research employs a descriptive qualitative approach with in-depth interview methods to analyze product development strategies, brand name selection, and strategies for entering the modern retail market. The findings indicate that product variations, appropriate brand name selection, packaging standardization, and understanding of modern retail market requirements are critical factors in successfully entering this market. This research highlights that the transition from traditional household production to modern retail-oriented operations requires strategic integration of product creativity and professional branding, demonstrating that medium-scale tempeh producers can effectively compete in modern retail environments through systematic approaches to product diversification, brand positioning, and market adaptation. The study also provides practical benefits for medium-scale tempeh industries in designing branding and marketing strategies to enter modern retail markets and underscores the importance of continuous innovation to enhance competitiveness.